Evaluating the Performance of Nonparametric Methods in Applied Statistics - Sami Atiyah Sayyid Al- Farttoosi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Nonparametric methods play a crucial role in applied statistics, particularly when dealing with data that does not conform to traditional parametric assumptions. This article aims to evaluate the performance of various nonparametric methods commonly used in applied statistics. The evaluation is conducted based on their ability to handle different types of data, their computational efficiency, and their robustness against outliers. The results of this evaluation provide researchers and practitioners with valuable insights into the strengths and limitations of nonparametric methods, enabling them to make informed decisions when choosing the appropriate method for their specific research questions.